UPAYA PENCEGAHAN PERKAWINAN DINI PASCA BERLAKUNYA UNDANG UNDANG NOMOR 16 TAHUN 2019 TENTANG PERUBAHAN UNDANG UNDANG NOMOR 1 TAHUN 1974 - Laila Safira Febriani; Soekarno Aburaerah; Salle Salle (Qawanin Jurnal Ilmu Hukum, 2020)
This research contains the efforts to prevent Early Marriage after the enactment of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974. This research aims to know the Prevention Process of Early Marriage Post-Law No.16 of 2019 concerning Amendments to Law No.1 of 1974 concerning Marriage At KUA Mariso Makassar several things are done by KUA Mariso to prevent early marriage. Some of these things are a form of implementation of the enactment of the latest rules amending Law No. 1 of 1974 concerning marriage, namely Law No. 16 of 2019. There are two things that KUA Mariso has done in preventing early childhood marriages. To further detail the two, the researcher will discuss them one by one as follows; 1. The Process of Integrating Understanding and Working on the Amendment of the Marriage Law for KUA Mariso's Civitas. Philipus M. Hadjon, Legal Protection for the People - A Study of its Principles, Handling by Courts in the General Court and the Establishment of State Administrative Courts (Surabaya: Bina Ilmu, 1987), Interview with DRS. Iwan Ridwansyah Head of KUA Mariso Makassar The Constitutional Court Decision No. 22 / PUU-XV / 2017, 22 is an assessment of matters relating to the implementation of marriage in Mariso Makassar which so far have been deemed inappropriate. With the latest regulations of Law Number 16 of 2019. In the facts discussed, it is said that the stakeholders, in this case, KUA employees and religious courts, modin, as well as sub-district and village heads, play a major role in shaping the general view of the minimum age of marriage according to the Marriage Law. This is certainly in line with or reinforced by the results of the survey which show that the minimum age of marriage for girls is 16 years old as a reference for most of the local community in determining the age limit for marriage